Sinergi Pembelajaran Akidah Akhlak dan Lingkungan Madrasah dalam Membentuk Karakter Jujur Peserta Didik di MTsN 5 Bantul - Rahmadani Akbar; Rahmad Alkhadafi; Ahyal Khairi; Zumratul Azka; Shofia Maulida (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study aims to explore the synergy between the teaching of Islamic creed and ethics (akidah akhlak) and the madrasa environment in shaping students’ honesty at MTsN 5 Bantul. The background of this research lies in the importance of honesty as a fundamental value in Islamic education, which is not only transmitted through classroom instruction but also cultivated through the school’s culture. This research employed a qualitative case study approach. Data were collected through observation, in-depth interviews with Islamic creed and ethics teachers, the principal, and eighth-grade students, as well as documentation of school programs. The findings reveal that the teaching of akidah akhlak serves as a normative foundation in instilling honesty values through lessons on shidiq, prophetic stories, real-life case discussions, and student reflections. The madrasa environment functions as a medium for habituating honesty through a religious culture, discipline, teacher role models, and everyday social interactions. In addition, character development programs such as Qur’anic recitation, morning prayers, and the Smile, Greeting, and Salutation (3S) movement further reinforce the internalization of honesty in a sustainable manner. The synergy between classroom learning, the school environment, and structured programs proves to be the key to successfully cultivating honesty, as students gain not only cognitive understanding but also affective experiences and practical application in daily school life. This study concludes that honesty-based character education must be carried out holistically by integrating akidah akhlak instruction with the madrasa culture. The findings are expected to serve as a reference for other madrasas in developing effective strategies for character education. Future research is recommended to conduct comparative studies across different madrasas or to explore other moral values such as trustworthiness, responsibility, and justice to provide a more comprehensive understanding of character education in Islamic contexts.